2021
DOI: 10.3390/en14020473
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Social Distancing on Electricity Demand Considering Temperature Dependency

Abstract: To mitigate the spread of the Novel Coronavirus (COVID-19), governments around the world have imposed social distancing policies ranging from minor social activity suspensions to full curfews. These social distancing policies have altered electricity consumption behaviors in numerous countries. Many governments imposed strict social distancing policies during a temperature transition season where the impacts of temperature variations are particularly important for the operation of the electric grid. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Understanding and anticipating the impacts of shocks like COVID-19 on the electricity sector is critical to maintaining grid reliability and building resilience to adverse events. Many recent works have attempted to estimate the decrease in consumption caused by the pandemic (Agdas and Barooah, 2020;Alhajeri et al, 2020;Alkhraijah et al, 2021;Bahmanyar et al, 2020;Cicala, 2020aCicala, , 2020bEdomah and Ndulue, 2020;EPIC, 2020;Eryilmaz et al, 2020;Halbrugge et al, 2021;Hauser et al, 2021;IEA, 2021;Jiang et al, 2021;Leach et al, 2020;Lopez Prol and O, 2020;Zachmann, 2020b, 2020a;Narajewski and Ziel, 2020;Percy and Mountain, 2020;Ruan et al, 2020;Santiago et al, 2021;Gillingham et al, 2020;Werth et al, 2020); however, they have been limited either by their timescale, geographic scope, modeling approach, and/or incomplete accounting of seasonal, weather, and temporal effects. Most other analyses are limited to individual countries or small groups of countries, particularly in the United States and Europe where high-resolution data are more readily available and only cover the initial stages of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding and anticipating the impacts of shocks like COVID-19 on the electricity sector is critical to maintaining grid reliability and building resilience to adverse events. Many recent works have attempted to estimate the decrease in consumption caused by the pandemic (Agdas and Barooah, 2020;Alhajeri et al, 2020;Alkhraijah et al, 2021;Bahmanyar et al, 2020;Cicala, 2020aCicala, , 2020bEdomah and Ndulue, 2020;EPIC, 2020;Eryilmaz et al, 2020;Halbrugge et al, 2021;Hauser et al, 2021;IEA, 2021;Jiang et al, 2021;Leach et al, 2020;Lopez Prol and O, 2020;Zachmann, 2020b, 2020a;Narajewski and Ziel, 2020;Percy and Mountain, 2020;Ruan et al, 2020;Santiago et al, 2021;Gillingham et al, 2020;Werth et al, 2020); however, they have been limited either by their timescale, geographic scope, modeling approach, and/or incomplete accounting of seasonal, weather, and temporal effects. Most other analyses are limited to individual countries or small groups of countries, particularly in the United States and Europe where high-resolution data are more readily available and only cover the initial stages of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Snow et al [86] found that a significant increase in household electricity consumption in Australia was directly related to the lockdowns. Also, the linkages between social distancing policy and ambient temperature and energy demand were identified in the study by Alkhraijah et al [87]. Chen et al [88] found that households used more energy during the pandemic, but only high-income households were more willing to pay for home energy management systems.…”
Section: Impact On Consumption and Habitsmentioning
confidence: 99%
“…These explanatory variables have also been specified in electricity price functions in previous studies: the prices of primary energy sources with calculations of electricity price cost elasticities [40,41,[52][53][54], CO 2 emission coupon prices [24,[55][56][57] and variations in local air temperature [58][59][60].…”
Section: Deregulation and Liberalization Of The Electricity Marketmentioning
confidence: 99%